Geniusze, prostacy, psychopaci – stereotypizacja w prezentacjach gier i graczy w serialach (rekonesans) - Olkusz, Ksenia (Śląskie Studia Polonistyczne, 2017)
The article deals with the stereotypical ways in which game players are represented in various TV series whose characters are constructed on the basis of well-worn (and not necessarily authentic) patterns. As a result, one-dimensional motifs of games and players lead to unvarying representations which tend to be bipolar. The screenwriters seem to be convinced that the only function of video games is escapism. The TV series characters are, therefore, constructed on the basis of definite patterns limited to specific personality models ranging from the genius to the simpleton with a low IQ. The article exemplifies stereotypes of games and players. It argues that the monochromatic way of presenting the players results – among others – from the fact that producers and screenwriters are willing to favour the expectations of average viewers and attempt to mirror some universally-acknowledged convictions which are not true.